A Jewish Construction of a Catholic Hero: David Levi’s "A Pio IX" - Grazi, Alessandro (Studies in Christian-Jewish Relations, 2012)
Along with liberals and patriots, many Italian Jews rejoiced on June 16, 1846, when Giovanni Maria Mastai Ferretti was elected Pope Pius IX. They expected the new Pope to reform the Papal State and to favor Italy’s unification, the goal of the Risorgimento national movement. Italian Jews suffered from a lack of civil rights, to different degrees within each Italian State. Therefore, they saw the Risorgimento as an opportunity to overthrow the regimes ruling on the different Italian regions and consequently as a way to achieve full civil emancipation. Italian Jewish intellectuals built a rich narrative on their support for Risorgimento. Part of this narrative is the poem “A Pio IX” (To Pius IX), composed by the Jewish writer David Levi (1816–1898) in 1846 to honor Pio Nono. This paper presents an analysis of Levi’s poem on a number of levels: historically, it provides further literary evidence of the Jews’ desire to praise Pope Pius IX and of their support for Risorgimento; concerning its content, it investigates Levi’s striking use, along with the more secular symbolism of the Enlightenment, of Catholic and Christological symbolism.